Between desire and pleasure : a Deleuzian theory of sexuality - Beckman, Frida (Plateaus., 2013)
"How is sexual pleasure inscribed into conceptions of the body, gender, health and the human? What is its role in the construction of these notions? And, most importantly, how can it contribute to an expansion of what they mean? Intervening into fields including posthumanist, disability, animal and feminist studies, and current critiques of capitalism and consumerism, Frida Beckman addresses these questions to recover a theory of sexuality from Deleuze's work"--Publisher's website.